Hubungan Keikutsertaan Kelas Ibu Hamil Resiko Tinggi Dengan Jenis Persalinan di Wilayah Puskesmas Trucuk II - Sri Wahyuni; Wiwin Rohmawati (Stikes Muhammadiyah Klaten, 2021)
The government program in reducing maternal mortality by implementing classes for high-risk pregnant women, with the activities of high-risk pregnant women classes, is expected to increase the number of normal deliveries, reduce the risk of childbirth and reduce the maternal mortality rate. The purpose of this study was to determine the relationship between high-risk pregnant women class participation and the type of delivery in the Trucuk II Public Health Center. This research method is descriptive correlational with cross sectional approach. In this study, the population used was all high-risk pregnant women in the working area of ​​the Trucuk II Klaten Public Health Center for the period July 1 to December 30 2019 as many as 134 respondents. The number of research samples were 34 respondents. Sampling with simple random sampling technique. The instrument used was a documentation sheet. Data analysis using Chi-squere test calculation. The results of the study, namely the participation of high-risk pregnant women class with the type of delivery showed that most of the 34 respondents were 21 (62%) who did not follow the type of vaginal delivery 15 respondents (68.2%) per abdominal 7 respondents (31.8%) . Respondents with the following category were 13 (38%) with 8 types of vaginal delivery (66.7%) per abdominal 4 respondents (33.3%)